Stochastic Spikes and Poisson Approximation of One-Dimensional Stochastic Differential Equations with Applications to Continuously Measured Quantum Systems - Kolb, Martin; Liesenfeld, Matthias (Annales Henri Poincaré)
Motivated by the recent contribution (Bauer and Bernard in Annales Henri Poincaré 19:653–693, 2018), we study the scaling limit behavior of a class of one-dimensional stochastic differential equations which has a unique attracting point subject to a small additional repulsive perturbation. Problems of this type appear in the analysis of continuously monitored quantum systems. We extend the results of Bauer and Bernard (Annales Henri Poincaré 19:653–693, 2018) and prove a general result concerning the convergence to a homogeneous Poisson process using only classical probabilistic tools.

Theoretical properties of quasi-stationary Monte Carlo methods - Wang, Andi Q.; Kolb, Martin; Roberts, Gareth O.; Steinsaltz, David (The Annals of Applied Probability)

Quasistationary distributions for one-dimensional diffusions with two singular boundary points - Hening, Alexandru; Kolb, Martin (Stochastic Processes and their Applications)
In the present work we characterize the existence of quasistationary distributions for diffusions on (0,∞) allowing singular behavior at 0 and ∞. If absorption at 0 is certain, we show that there exists a quasistationary distribution as soon as the spectrum of the generator is strictly positive. This complements results of Collet et al. and Kolb/Steinsaltz for 0 being a regular boundary point and extends results by Collet et al. on singular diffusions. We also study the existence and uniqueness of quasistationary distributions for a class of one-dimensional diffusions with killing that arise from a biological example and which have two inaccessible boundary points (more specifically 0 is natural and ∞ is entrance).

Feuilletons als Bildarchive historischen Wissens. Städteminiaturen der Weimarer Republik - Öhlschläger, Claudia (KulturPoetik, Heft 2)

Vitamin D and the Risk of Depression: A Causal Relationship? Findings from a Mendelian Randomization Study - Libuda, Lars; Laabs, Björn-Hergen; Ludwig, Christine; Bühlmeier, Judith; Antel, Jochen; Hinney, Anke; Naaresh, Roaa; Föcker, Manuel; Hebebrand, Johannes; König, Inke R.; Peters, Triinu (Nutrients)
While observational studies show an association between 25(OH)vitamin D concentrations and depressive symptoms, intervention studies, which examine the preventive effects of vitamin D supplementation on the development of depression, are lacking. To estimate the role of lowered 25(OH)vitamin D concentrations in the etiology of depressive disorders, we conducted a two-sample Mendelian randomization (MR) study on depression, i.e., “depressive symptoms” (DS, n = 161,460) and “broad depression” (BD, n = 113,769 cases and 208,811 controls). Six single nucleotide polymorphisms (SNPs), which were genome-wide significantly associated with 25(OH)vitamin D concentrations in 79,366 subjects from the SUNLIGHT genome-wide association study (GWAS), were used as an instrumental variable. None of the six SNPs was associated with DS or BD (all p > 0.05). MR analysis revealed no causal effects of 25(OH)vitamin D concentration, either on DS (inverse variance weighted (IVW); b = 0.025, SE = 0.038, p = 0.52) or on BD (IVW; b = 0.020, SE = 0.012, p = 0.10). Sensitivity analyses confirmed that 25(OH)vitamin D concentrations were not significantly associated with DS or BD. The findings from this MR study indicate no causal relationship between vitamin D concentrations and depressive symptoms, or broad depression. Conflicting findings from observational studies might have resulted from residual confounding or reverse causation.

Risk factors for a low weight gain in the early stage of adolescent anorexia nervosa inpatient treatment: findings from a pilot study - Knoll-Pientka, Nadja; Bühlmeier, Judith; Peters, Triinu; Albrecht, Muriel; Adams, Frederike; Wustrau, Katharina; Teufel, Martin; Hebebrand, Johannes; Föcker, Manuel; Libuda, Lars (Eating and Weight Disorders - Studies on Anorexia, Bulimia and Obesity)

Clinical Trials Required to Assess Potential Benefits and Side Effects of Treatment of Patients With Anorexia Nervosa With Recombinant Human Leptin - Hebebrand, Johannes; Milos, Gabriella; Wabitsch, Martin; Teufel, Martin; Führer, Dagmar; Bühlmeier, Judith; Libuda, Lars; Ludwig, Christine; Antel, Jochen (Frontiers in Psychology)

Retrospektive Evaluation der Umsetzung einer klinikinternen Handlungsanweisung zur Ernährungstherapie von Intensivpatienten - Dresen, Ellen; Weißbrich, Carsten; Bühlmeier, Judith; Weisheit, Christina; Egert, Sarah; Putensen, Christian; Stehle, Peter (Aktuelle Ernährungsmedizin)
Zusammenfassung Hintergrund Die begleitende Ernährungstherapie von Intensivpatienten stellt eine besondere Herausforderung in der klinischen Routine dar und erfordert die Implementation von leitlinienbasierten Handlungsanweisungen. Methoden In einer retrospektiven Analyse wurde die Umsetzung der klinikinternen Handlungsanweisung zur Ernährung kritisch kranker Patienten (Gültigkeitszeitraum September 2013 bis Januar 2016) sowie der Anordnung zur Ernährungstherapie auf einer operativen Intensivstation des Universitätsklinikums Bonn an Daten des Ernährungsmanagements von 31 Langzeit-Intensivpatienten (7 Frauen; Alter: 60 ± 17 Jahre; BMI: 28 ± 10 kg/m2; Dauer des Intensivaufenthalts: 34 ± 16 Tage) evaluiert. Ausgewertet wurden Daten zur Initiation, zum Ablauf sowie zur Berechnung und Umsetzung der Energie- und Proteinzufuhr. Dazu wurden jeweils die im Stationsalltag angeordnete bzw. protokollierte Zufuhr, die protokollierte Zufuhr abzüglich Reflux sowie das retrospektiv beurteilte Ziel, welches durch die klinikinterne Handlungsanweisung indiziert war, miteinander verglichen (linear gemischtes Modell). Ergebnisse Mit der enteralen Ernährung wurde im Mittel an Tag 4 ± 3, mit der (supplementierenden) parenteralen an Tag 3 ± 3 begonnen. Die Energiezufuhr wurde mit Korrekturfaktoren als ein Vielfaches des Grundumsatzes nach Harris & Benedict berechnet. Der individuell verwendete Korrekturfaktor zur Berechnung der angeordneten Energiezufuhr wich über die gesamte Dauer des stationären Aufenthalts 0,1 ± 0,3 vom retrospektiv als angemessen erachteten Korrekturfaktor ab. Hieraus resultierte eine Abweichung der angeordneten Energiezufuhr vom Energieziel von 123 ± 528 kcal/24 h. Insbesondere in den Tagen 1 – 10 betrug die Abweichung des angeordneten vom retrospektiv als angemessen erachteten Korrekturfaktor 0,2 ± 0,4, was zu einer Differenz zwischen angeordneter Energiezufuhr und Energieziel von 426 ± 772 kcal/24 h führte. Die protokollierte Proteinzufuhr lag über die gesamte Behandlungsdauer bei 1,1 g/kg KG/24 h, während das retrospektiv ermittelte Proteinziel 1,0 g/kg KG/24 h betrug. Schlussfolgerung Die Analyse liefert vertrauenswürdige Daten zur Implementation einer individualisierten Ernährungstherapie von Langzeit-Intensivpatienten auf einer operativen Intensivstation; diese können zur Weiterentwicklung von entsprechenden Handlungsanweisungen genutzt werden. Defizite bestehen sowohl im zeitlichen Ablauf (zu später Beginn) als auch in der Anordnung der Energie-/Nährstoffzufuhr. Umfassende Schulungen des ärztlichen und pflegerischen Personals zur Anwendung/Umsetzung der Ernährungstherapie sind zu empfehlen.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Ansichtspostkarte - Öhlschläger, Claudia (Enzyklopädie der kleinen Formen [Audio-Enzyklopädie des Podcasts microform], URL: www.kleine-formen.de/enzyklopaedie-ansichtspostkarte)

Georges de Scudéry et le théâtre - Schlieper, Hendrik; Steigerwald, Jörn (Papers on French Seventeenth Century Literature, 91)

Georges de Scudéry et le théâtre - Steigerwald, Jörn (Papers on French Seventeenth Century Literature XLVI, 91)

Assessing dimensions of inclusion from students’ perspective – measurement invariance across students with learning disabilities in different educational settings - Knickenberg, Margarita; Zurbriggen, Carmen; Venetz, Martin; Schwab, Susanne; Gebhardt, Markus (European Journal of Special Needs Education)
Keywords: Developmental and Educational Psychology; Health Professions (miscellaneous); Education

'Runzelsex' im Kino. Die Sexualisierung alter Körper in Andreas Dresens Wolke 9 zwischen Provokation und Subversion - Süwolto, Leonie (Figuren des Provokativen und Subversiven. Körper und Sexualität multimedial)

La novelística italiana y la comedia de Lope de Vega - Schlieper, Hendrik (Los pre-textos del teatro áureo español. Condicionantes literarios y culturales. (Biblioteca Áurea Hispánica, 128))

,Le Romain‘ selon Scudéry – La Mort de César - Schlieper, Hendrik (Papers on French Seventeenth Century Literature, 91)

Geschichtsbetrachtung jenseits der Norm: Städte- und Reisefeuilletons von Franz Hessel, Joseph Roth und Siegfried Kracauer als politische Reflexionsräume und kleine Bildarchive historischen Wissens - Öhlschläger, Claudia (Konformieren. Festschrift für Michael Niehaus)

Lemma „Wild/Wildnis" - Öhlschläger, Claudia (Neue Romantik. Eine kleine Literaturgeschichte 1989-2019)

Introduction: une apologie de Georges de Scudéry et de son théâtre - Steigerwald, Jörn (Georges de Scudéry et le théâtre. Papers on French Seventeenth Cenrury Literature XLVI, 91)

Un combat d'amour en pastoral: la tragi-comédie "Ligdamen et Lidias ou La ressemblance“ - Steigerwald, Jörn (Georges de Scudéry et le théâtre. Papers on French Seventeenth Cenrury Literature XLVI, 91)

Sinnliche Machtspiele: Die Erotik des Scrabblespiels in Margaret Atwoods Roman und Bruce Millers Serienadaption von "The Handmaid's Tale" - Hannebohm, Ronja (Erotik in Literatur und Theater)

Operatoren „to go“. Ein Arbeitsheft zum Nachschlagen und Üben für das Fach Deutsch

Feilke revisited. 60 Stellenbesuche

Schreiben zu Texten. Fördermagazin Sekundarstufe Deutsch 4/2019

Operatoren „to go“. Praxis Deutsch 274

Was ist zu tun? Operatorenformulierungen - Rezat, Sara; Feilke, Helmuth (Operatoren „to go“. Ein Arbeitsheft zum Nachschlagen und Üben für das Fach Deutsch)

Sprache und Sprachgebrauch untersuchen und reflektieren - Rezat, Sara (Fachdidaktik Deutsch. 3., überarbeitete und aktualisierte Auflage.)

Fachspezifische Leistungsbewertung und –beurteilung - Rezat, Sara (Fachdidaktik Deutsch. 3., überarbeitete und aktualisierte Auflage)

Schreiben zu Texten. Potenziale eines vielgestaltigen Aufgabensettings für das Lesen und Schreiben nutzen - Rezat, Sara; Schüler, Lisa (Fördermagazin Sekundarstufe Deutsch 4/2019)

Filme im Podcast unter die Lupe nehmen - Rezat, Sara; Schüler, Lisa (Fördermagazin Sekundarstufe Deutsch 4/2019, (+Downloadmaterial))

Textdidaktische Gattungen: Etüden im Schreibunterricht? - Rezat, Sara (Feilke revisited. 60 Stellenbesuche)

Operatoren „to go”. Prozedurenorientierter Schreibunterricht. Basisartikel - Rezat, Sara; Feilke, Helmuth (Praxis Deutsch 274)

CLIL(iG) im Literaturunterricht der Sekundarstufe I? Konzepte der Fremdsprachendidaktik in einem integrativen Deutschunterricht am Beispiel von Emine Sevgi Özdamars „Karagöz in Alamania. Schwarzauge in Deutschland“ - Zierau, Cornelia; Kofer, Martina (Jahrbuch Deutsch als Fremdsprache 2016)

Stifterverband für die Deutsche Wissenschaft e.V.: Lehrkräftebildung für die Schule der Vielfalt. Eine Handreichung des Netzwerks Stark durch Diversität. (Mitautorin) - Zierau, Cornelia

Türkisch-deutsche Studien Jahrbuch 2018: Übersetzung als Kulturaustausch

Die Wissenschaftler und das verantwortliche Handeln im schweizerischen Drama. Friedrich Dürrenmatts Physiker Möbius und Lukas Bärfuss' Mediziner Gustav Strom - Famula, Marta (Vom Gipfel der Alpen... Das schweizerische Drama und Theater im 20. und 21. Jahrhundert)

„…ein gewisses Verhältnis zum Leben“. Die lebensweltliche Bedeutung der Schinkensemmel im Erzählwerk Thomas Manns - Famula, Marta (Dinge im Werk Thomas Manns (= inter/media 11))

Mechanical joining without auxiliary element by cold formed pins for multi-material-systems - Kraus, M.; Frey, P.; Kleffel, T.; Drummer, D.; Merklein, M. (AIP Conference Proceedings)

Vollvalidiertes thermisches Netzwerk eines RWDR- Ersatzsystems - Burkhart, C; Heimes, J; Weyrich, D; Magyar, Balázs; Sauer, B

Downturns are a better time for deal hunting - Kengelbach, Jens; Keienburg, Georg; Gell, Jeff; Nielsen, Jesper; Bader, Maximilian; Degen, Dominik; Sievers, Sönke (The 2019 M&A-Report)

Determinants of Financial Misreporting: A Survey of the Financial Restatement Literature - Sievers, Sönke; Sofilkanitsch, Christian

Oblique evanescent excitation of a dielectric strip: A model resonator with an open optical cavity of unlimited Q - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Optics Express)
A rectangular dielectric strip at some distance above an optical slab waveguide is being considered, for evanescent excitation of the strip through the semi-guided waves supported by the slab, at specific oblique angles. The 2.5-D configuration shows resonant transmission properties with respect to variations of the angle of incidence, or of the excitation frequency, respectively. The strength of the interaction can be controlled by the gap between strip and slab. For increasing distance, our simulations predict resonant states with unit extremal reflectance of an angular or spectral width that tends to zero, i.e. resonances with a Q-factor that tends to infinity, while the resonance position approaches the level of the guided mode of the strip. This exceptionally simple system realizes what might be termed a “bound state coupled to the continuum”.
Keywords: tet_topic_waveguides

Sonderpädagogik als Erfahrungs- und Praxiswissenschaft. Geistes-, sozial- und kulturwissenschaftliche Perspektive - Dederich, M; Ellinger, S.; Laubenstein, Désirée

Beurteilung der Leistungsfähigkeit von Schmierstoffen mittels eines FZG Prüfstandes - Keßler, A; Elkenkamp, P; Magyar, Balázs; Mayer, C (Tribologie und Schmierungstechnik)

Teamentwicklung und Teamkooperation - Guthöhrlein, K.; Laubenstein, Désirée; Lindmeier, C.

Reibenergie basierte Verschleißsimulation für Radialwellendichtringe - Foko Foko, F; Sauer, B; Magyar, Balázs

The ‘Learning Office’ as an Approach for Inclusive Education in Mathematics: Opportunities and Challenges - Laubenstein, Désirée; Guthöhrlein, Kirsten; Lindmeier, Christian; Scheer, David; Sponholz, Dirk (In: Kollosche, D.; Marcone, R.; Knigge, M.; Godoy Penteado, M.; Skovsmose, O. (Hrsg.). Inclusive Mathematics Education. State-of-the-Art Research from Brazil and Germany)

Das Praxissemester von angehenden Lehrkräften - Caruso, Carina

Praxissemester (Religion) in NRW: Bilanz und Perspektiven - Caruso, Carina; Woppowa, Jan
Since the winter semester 2014 / 2015 long-term internships have become an integral part of the second master semester at universities in North Rhine-Westphalia. One aim is to improve the development of competencies of prospective teachers. This anthology provides an insight into perspectives of long-term internships in North Rhine-Westphalia referring especially to internships of those prospective teachers, who are going to be teachers for religious education. First Bardo Herzig and Christoph Wiethoff present the plan, the structure and the content of long-term internship at Paderborn University. They take pedagogy as their example. Petra Herzmann and Anke B. Liegmann provide a comprehensive survey of qualitative research on long-term internships and present ideas of a qualitative research programme. Carina Caruso and Andreas Seifert focus on the development of pedagogical knowledge of prospective teachers of religious education during the practice phase. Malte Kling gives a summary of his thesis referring to the change of roles of prospective teachers of religious education. Guido Hunze und Gudrun Lohkemper have a look at the relation between theory and practice for a successful professionalization. Norbert Brieden and Monika Tautz compare the accompaniment of students at Cologne and Wuppertal University and put forward an impetus for teaching at university. Mirjam Zimmermann looks at spirituality in internships. Guido Meyer and Carsten Misera give a definition of heterogeneity as a starting point of the development of the teacher habitus. Christoph Vogelsang and Ulrich Feeser-Lichterfeld contribute to a further combination of perspectives on internships. Carina Caruso and Jan Woppowa give a final summary looking especially at future tasks of the design of long-term internships in theology.

On the nomological net of (non-) workaholic subtypes - Ontrup, Greta; Patrzek, Justine (Career Development International)

Estimation of Nematic Order Parameters via Haller Analysis of 1H NMR Spectra of Liquid Crystals - Tang, Ming-xue; Schmidt, Claudia (Chinese Journal of Magnetic Resonance)
The Haller relationship was applied to estimate the nematic order parameter S from 1H NMR spectra of fully protonated liquid crystals aligned in the magnetic field. The NMR line shapes were approximated as doublets of very broad peaks. Both the temperature-dependent doublet Splitting and the full width at half maximum of the whole spectra were used for Haller extrapolation. The order parameters obtained with the proposed approach for 4-cyano-4'-pentylbiphenyl (5CB) and the nematic mixture E7 were found to be in good agreement with previously reports.
Keywords: nematic liquid crystal; order parameter; Haller analysis; 1H NMR